2018
DOI: 10.3892/etm.2018.5761
|View full text |Cite
|
Sign up to set email alerts
|

miR-372 promotes breast cancer cell proliferation by directly targeting LATS2

Abstract: MicroRNAs (miRs) have previously been demonstrated to be important in the tumorigenesis and progression of breast cancer. miR-372 was previously revealed to be involved in various types of human cancer, however its function in breast cancer remains largely unknown. The present study demonstrated that miR-372 is frequently overexpressed in breast cancer cell lines and tissues. The downregulation of miR-372 markedly inhibited cell proliferation, arrested the cell cycle in the G1/S phase, and increased the apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…miRNAs function as either oncogenes or tumor suppressors, playing crucial roles in tumorigenesis, tumor invasion and metastasis 5 . In recent years multiple studies have revealed the altered expression of miRNAs which play a role in the development and progression of diverse cancers including oral squamous cell carcinoma 6 – 8 . Increased expression of microRNAs including miR-155 and miR-23a, have been observed in oral cancer patients that are tobacco chewers compared to non-chewers 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs function as either oncogenes or tumor suppressors, playing crucial roles in tumorigenesis, tumor invasion and metastasis 5 . In recent years multiple studies have revealed the altered expression of miRNAs which play a role in the development and progression of diverse cancers including oral squamous cell carcinoma 6 – 8 . Increased expression of microRNAs including miR-155 and miR-23a, have been observed in oral cancer patients that are tobacco chewers compared to non-chewers 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are reported to be widely involved in multiple biological processes, including cellular proliferation, differentiation, migration and invasion, primarily through binding the 3′-untranslated region (3′UTR) of target mRNAs, inhibiting their translation ( 7 9 ). The altered expression of miRNAs was found to be associated with the progression of various tumors, including pancreatic, lung and breast cancer ( 10 12 ). miR-25-3p was reported to target Sema4C in CC cells thereby regulating the epithelial-mesenchymal transition ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are supported by third-party annotations in two databases, HMDD3.2 and dbDEMC. For example, miR-150 and miR-372 can promote the proliferation and growth of Breast Neoplasms cells by targeting the pro-apoptotic purinergic P2X7 receptor and LATS2 respectively (Huang et al, 2017;Cheng et al, 2018). MicroRNA-130a targets RAB5A to inhibit the proliferation, invasion and migration of Breast Neoplasms cells (Pan et al, 2015).…”
Section: Case Studymentioning
confidence: 99%